If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2B + -6 = 4B Reorder the terms: -6 + 2B = 4B Solving -6 + 2B = 4B Solving for variable 'B'. Move all terms containing B to the left, all other terms to the right. Add '-4B' to each side of the equation. -6 + 2B + -4B = 4B + -4B Combine like terms: 2B + -4B = -2B -6 + -2B = 4B + -4B Combine like terms: 4B + -4B = 0 -6 + -2B = 0 Add '6' to each side of the equation. -6 + 6 + -2B = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -2B = 0 + 6 -2B = 0 + 6 Combine like terms: 0 + 6 = 6 -2B = 6 Divide each side by '-2'. B = -3 Simplifying B = -3
| 3-(3x-8)=4y-5 | | (4c-6c+5)(4c-2c-1)= | | lnx-2lnx=3 | | 6x-4=20x+3 | | 6x-23+x+54=180 | | 4x+2x(x+4)= | | -4x-6(-2+4)=64 | | 2x+y-z=7z | | -4x-6(-2+4)=64 | | 3x-1=-3x+3 | | 3x-1=-3x+3 | | -5x+-2=-2X+4 | | -6x-5(-3x-3)=60 | | 114=2x+3x | | 5x+7y=3890 | | 8x+7y-5-5x+6y-3= | | -2x-2(-5x-4)=-80 | | 15+4y-1=15y-13-2y | | y+(y-2)2=2 | | 3x-n=7+n | | 25-13=3(x-1) | | -13.9=b+17.1 | | r+7= | | 15-44=3(x-4)-5 | | 3x+(x-5)=15+4 | | -16+13=m-2 | | -3x=8-(-1) | | 3w+5-2w+7= | | 2x^6=-3 | | 5mn-2m(m-2n)= | | 7(x+2)-3x=4(x-1)+10 | | -13.9=b-17.1 |